Features of intellectual functions inhibition among Ukrainian boxers: A sociocultural study - Ivanchenko, Andreyanna; Timchenko, Olexander; Zamperini, Adriano; Testoni, Ines; Gant, Olena; Malyk, Iaroslava (European Journal of Mental Health, 2020)
The effects of boxing’s extreme aggressive conditions in training and competitive activity insportsmen’s mental working capacity still remains under-explored. While the neurophysiologicaleffects caused by micro traumas to the brain have been extensively studied, less attention has beenpaid to the psychological consequences. This article reports on our study of the features of mentaloperations efficiency in Ukrainian boxers. The study involved athletes (n = 168, gender: men, averageage: 25.5 ± 6.2 years), who were engaged in boxing and kickboxing in the Ukraine’s easternregion. A ‘Classification’ method was used: a set of 70 cards with the images of various objects,plants, and living beings was given with instructions to arrange the items into groups in such a waythat the objects in each concrete group possess common properties. Athletes were divided intogroups, depending on the level of their sport qualification. Adopting the Vygotskian perspective,this study shows correlations between the productivity of boxers’ thinking processes and the levelof their sport skills: highly qualified sportsmen have many more well-marked thinking processdefects than the sportsmen of the 2nd and 3rd categories. We observed a decrease in the generalizationlevel, reduction in speed, deterioration of neurodynamic characteristics and criticalityprocesses nearly in all participants. Exhaustibility and decrease in mental working capacity, impulsivenessof thinking, and its unproductive transformation were marked more often among thehighly skilled boxers. A discussion on the cultural redefinition of this sport and on the necessaryrehabilitative treatments is then presented.